The rush : a novel [large type] - Lewis, Beth, 1986- (Center Point Large Print, 2026)
"'Gold fever has taken him. I believe he means to kill me' . . . Canada, 1898. The Gold Rush is on in the frozen wilderness of the Yukon. Fortunes are made as quickly as they're lost, and Dawson City has become a lawless settlement. In its midst, three women are trying to find their place on the edge of civilization. Journalist Kate, along with her dog Yukon, has travelled hundreds of miles after receiving a letter from her sister warning that her husband means to kill her. Martha's hotel and livelihood are under threat from the local strongman, who is set on buying up the town. And down by the river, where gold shimmers from between the rocks, Ellen feels her future slip away as her husband fails to find the fortune they risked so much to seek. When a woman is found murdered, Kate, Martha, and Ellen find their lives, fates, and fortunes intertwined. But to unmask the killer, they must navigate a desperate land run by dangerous men who will do anything for a glimpse of gold . . ."--